Animal Models of Hypertension: A Scientific Statement From the American Heart Association. Issue 6 (June 2019) - Lerman, Lilach O.; Kurtz, Theodore W.; Touyz, Rhian M.; Ellison, David H.; Chade, Alejandro R.; Crowley, Steven D.; Mattson, David L.; Mullins, John J.; Osborn, Jeffrey; Eirin, Alfonso; Reckelhoff, Jane F.; Iadecola, Costantino; et al.
Abstract : Hypertension is the most common chronic disease in the world, yet the precise cause of elevated blood pressure often cannot be determined. Animal models have been useful for unraveling the pathogenesis of hypertension and for testing novel therapeutic strategies. The utility of animal models for improving the understanding of the pathogenesis, prevention, and treatment of hypertension and its comorbidities depends on their validity for representing human forms of hypertension, including responses to therapy, and on the quality of studies in those models (such as reproducibility and experimental design). Important unmet needs in this field include the development of models that mimic the discrete hypertensive syndromes that now populate the clinic, resolution of ongoing controversies in the pathogenesis of hypertension, and the development of new avenues for preventing and treating hypertension and its complications. Animal models may indeed be useful for addressing these unmet needs.